1989
DOI: 10.1021/j100355a046
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman scattering from liquid metal films formed from silver sols

Abstract: The production of mobile silver films at the interface between an aqueous silver sol and a solution of a transition-metal complex in an organic solvent is reported. The films exhibit very similar physical properties to those described in a recent report (J. Phys. Chem. 1988, 92, 5754) but are produced by a simpler method of shaking together the sol and a solution of metal complex in a nonaqueous solvent. The phenomenon has been observed for several complexes of Cu1, Fe11, and Fem and affords a novel method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 0 publications
1
58
0
Order By: Relevance
“…To avoid assembly at the solid interface, which generally requires chemical treatment prior to assembly 29 , NP films formed at the interface between two immiscible phases, such as a liquid-liquid interface (LLI) or liquid-air interface (LAI), can be used 30,31 . The interfacial tension between such phases is reduced by the adsorption of NPs 32 which ultimately stabilizes the assembly 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…To avoid assembly at the solid interface, which generally requires chemical treatment prior to assembly 29 , NP films formed at the interface between two immiscible phases, such as a liquid-liquid interface (LLI) or liquid-air interface (LAI), can be used 30,31 . The interfacial tension between such phases is reduced by the adsorption of NPs 32 which ultimately stabilizes the assembly 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] The films have remarkable properties, they typically have a highly reflective metallic appearance, despite being just one nanoparticle layer thick, can self-heal if damaged and provide very strong SERS enhancements. They can be prepared by shaking an aqueous metal colloid with an immiscible non-aqueous solvent containing "modifier" compound which was originally believed to adsorb to the particles, increasing their hydrophobicity.…”
Section: Characterisation Of Sensor Surfacesmentioning
confidence: 99%
“…This was supported by observation of strong SERS signals of the modifiers from the MeLLFs. [23] However, recent studies have shown there are compounds which promote MeLLF formation without surface adsorption as shown by the SERS spectra of the MeLLFs, which are identical to those of the parent colloid. [24] This SERS evidence was key in showing that there are two separate mechanisms for MeLLF formation based on increased particle hydrophobicity and/or decreased Coulombic repulsion between the particles.…”
Section: Characterisation Of Sensor Surfacesmentioning
confidence: 99%
“…Stable interfacial assemblies of silver nano-particles have been previously reported in the literature and are known as MEtal Liquid-Like Films, or MELLFs (Yogev & Efrima 1988;Gordon et al 1989). MELLFs were originally used in spectroscopic experiments to study the chemicals that coated the colloidal grains.…”
Section: Nanoengineered Liquid Mirrorsmentioning
confidence: 99%